Application of LF-NMR to the characterization of camellia oil-loaded pickering emulsion fabricated by soy protein isolate. (March 2021) - Wang, Chen; Wang, Xin; Liu, Caiyun; Liu, Conghui
Abstract: In this study, the camellia oil-loaded Pickering emulsion stabilized by soybean protein isolate (SPI) was selected, and low-field nuclear magnetic resonance were adopted to characterize the emulsion transformation process besides conventional characterization index. Results showed that the T2 distribution of SPI dispersion only showed one hydrogen pool, and Tcur, T2W and T2 all decreased with the increase of SPI concentration, indicating faster decay and lower proton mobility, which was companied by increasing particle diameter. The addition of NaCl and heating (95 °C, 15 min) can speed up the relaxation decay, increase the surface hydrophobicity and reduce the nanoparticle diameter. As for the emulsion, three hydrogen populations were observed on T2 distribution. Based on the correlation results, the hydrogen pools were successfully attributed to oil and water phase, respectively. Meanwhile, with the increase of oil volume fraction (0.1–0.6), the Tcur and T2W tended to decrease, the absorbed protein percentage (AP%) and the shear viscosity tended to increase, while the droplet diameter only increased significantly when ϕ was below 0.3. Lastly, the T2 distribution of the oleogel showed two hydrogen populations, and the population (T22 ) could be interpreted as the mobility of protons in oil molecules, which accounted for more than 95% of the total signal. Although the elastic properties of oleogel became weaker with the increase of ϕ, the Tcur and T2W were relatively stable. However, it was significantly distinctive from that of SPI dispersion and emulsion. In summary, LF-NMR could be used for the rapid characterization of emulsion. Graphical abstract: Image 1 Highlights: The LF-NMR spectra can be used to rapidly characterize the emulsion. Relaxation signals were influenced by several processing parameters. Relaxation behavior of the sample at different preparation stage was different. The hydrogen pools were attributed to oil and water phase, respectively.